TECHNICAL ASSESSMENT AND BUSINESS CAPTURE PUSH NET FISHERIES IN SELAT AKAR VILLAGE, TASIK PUTRIPUYU DISTRICT, MERANTI ISLAND REGENCY - Syofyan, Silfia; Brown, Arthur; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT   This research was conducted in August in the Selat Akar Village, Tasik Putripuyu District, Island Meranti Regency, Riau Province. This study aims to analysis the technical and financial analysis of the business valuation or push net fishing gear business towards fishing that is applied by fishermen in terms of responsible fisheries criteria. The method used in this study is a survey method which is done by direct observation to the field and interviews with fishermen, equipped with technical and financial aspects related to this research. The data obtained is processed with technical analysis, environmental friendliness analysis and financial analysis. Push net fishing gear is different from push net fishing gear in general because this fishing gear is operated on the surface with a depth of ± 1 m, while the catch is anchovy (Stolephorus sp). This fishing gear has been weighted using 5 FAO criteria which show that this fishing gear is very environmentally friendly. This fishing gear is also feasible to proceed because the catches obtained more than operational costs in one year with a profit (Rp.53.488.334), so that capital returns are also quickly carried out. Keywords : Push net, Stolephorus sp, Environmentally friendly